Circ_0004904 suppresses trophoblast cell proliferation, invasion and migration in preeclampsia via upregulating the expression of DNA damage inducible alpha by interacting with miR-19a-3p. Issue 4 (16th February 2023) - Chu, Zhenhao; Wang, Yang; Zhang, Shuo; Cao, Pin
ABSTRACT: Preeclampsia (PE) is the most common complication in the pregnancy of women. PE progression was found to be associated with dysregulated circular RNAs (circRNAs), and we aimed to explore the pathological mechanism with circ_0004904 in PE. The circ_0004904, microRNA-19a-3p (miR-19a-3p) and DNA damage inducible alpha (GADD45A) were quantified via reverse transcription-quantitative polymerase chain reaction assay. Trophoblast cell behaviors were examined by cell viability using Cell Counting Kit-8 assay, cell proliferation using EdU assay, cell apoptosis using flow cytometry, cell invasion using transwell assay and migration using wound healing assay. Western blot was used for protein analysis of epithelial mesenchymal transition (EMT) and GADD45A. Dual-luciferase reporter assay and RNA immunoprecipitation assay were used for target interaction analysis. The circ_0004904 upregulation was detected in placenta tissues from PE patients. Trophoblast cell proliferation, invasion, migration and EMT were repressed but cell apoptosis was promoted after overexpression of circ_0004904. Circ_0004904 acted as a miR-19a-3p sponge in trophoblast cells, and all regulatory effects of circ_0004904 on trophoblast cell behaviors were reversed by miR-19a-3p upregulation. The miR-19a-3p directly targeted GADD45A and miR-19a-3p downregulation inhibited trophoblast cell development through elevating the GADD45A level. Moreover, circ_0004904 enhanced the expression of GADD45A via sponging miR-19a-3p. Our results elucidated that circ_0004904 reduced proliferation and cell motility of trophoblast cells via the miR-19a-3p-mediated GADD45A level elevation, indicating the involvement of circ_0004904/miR-19a-3p/GADD45A in PE progression.